An economy of access is opening for business: five strategies for success. Issue 4 (15th July 2014) - Denning, Stephen
Abstract : Purpose: – Many new businesses are being formed to offer shared products and services. The author describes this trend as an access economy, which offers customers the benefits of disintermediation - tourist accommodations without hotel chains, local transportation without taxi companies, peer-to-peer lending without banks, retail storefronts with brokers and leases. The paper aims to analyse the factors that are driving its growth. Design/methodology/approach: – The author offers five strategies for success in the access economy and describes how firms are using them to gain competitive advantage. Findings: – The sharing economy has produced three phenomena – the shredding of vertical value chains, the creation of vast new horizontal value chains, and the social change of people preferring access to ownership or accepting the benefits of access. Together they bring significant economic and social changes to business and society. Practical implications: – Some companies are beginning to adjust to the generational shift from ownership to access by deemphasizing the sale of things and refocusing their business practices on managing every aspect of their client's value chain – what they call being a "solution provider." Social implications: – Instead of planning their lives on the premise of acquiring and owning more private property, a new generation of web adventurers, mostly young people, is finding meaning and satisfaction in having shared access to things and interacting with other people in the process. Originality/value: – Each business will likely have a unique take on the best way to compete is this emerging environment given how much its customers value access and accept sharing. The author's five possible strategies provide a starting point for corporate competitive scenarios.